A REVIEW ON DEVELOPMENT OF 3D ADVENTUROUS SERIOUS GAME: THE SEASONAL RUN - Nithiyaa Muniandy, Sathya Manoharan, Kohilah Miundy (International Journal of Advanced Science and Technology, 2020)
Gaming industry is a boosting phenomenon and the focus of games has grown from entertainment to serious learning. Previously, tremendous amount of games were produced with the focus on adventure, action-adventure, role-play, racing, multiplayer, casual play and many more. However, current trend in gaming world has transformed the action or adventure game to an immersive educational game, which include pedagogical aspect to enable learning process during the play. This paper discusses on the development of three-dimensional (3D) adventurous serious game called Seasonal Run using Unity Game Engine by a group of students. The game was developed based on phases available on the traditional Game Development Life Cycle (GDLC) namely, initiation, preproduction, production, alpha testing and beta testing and finally to release but each development phases has been refined with detailed context to simplify the game production. This guideline method able to produce a wholesome game with interesting features of adventure game such as exciting storyline, fun and realism, unceasing challenge, immediate and useful rewards, target to achieve, replayability and also include some serious game elements such as engaged learning, knowledge through experience and problem solving skills. After the deployment, a prototype framework was developed to differentiate educational and entertainment module.